NIPPLE SPARING MASTECTOMY: A LITERATURE REVIEW - Pires, Douglas de Miranda; Fonseca, Eduardo José Souza da; Valadares, Carolina Nazareth; Andrade, Raffaela Levy; Nascimento, Mariana dos Santos; Albuquerque, Anna Maria Fonseca (Mastology, 2018)
Introduction: The treatment of carcinoma in the early stages of breast cancer has achieved significant evolution in recent years. These developments culminated in the replacement of conventional mastectomy by more conservative techniques, such as nipple sparing mastectomy (NSM). This technique has been gaining space due to the fact that, in skin sparing mastectomy, the removal of the areola-papillary complex substantially compromises aesthetic results; despite recent and varied techniques of reconstructing of this complex, the dissatisfaction observed is of about 36% of the patients undergoing this procedure. Objective: Reviewing the literature about nipple sparing mastectomy of the areola-papillary complex, its oncological safety, selection criteria, surgical techniques and complications. Discussion: Oncologic safety is acceptable as long as matters such as selection criteria, low rate of complications and varied and feasible surgical techniques are in compliance. Conclusion: We found a current trend, in various institutions, to the standardization of the nipple sparing mastectomy for the treatment of early breast cancer cases. In order to achieve great results with this technique we need a multidisciplinary action between the breast surgeon, the clinical oncologist and the radiation therapy specialist. This technique shows excellent oncologic safety and low rates of complications when careful patient selection is associated with a surgeon’s expertise. However, larger and longer follow-up series of patients undergoing NSM are still required.